Phase segregation in thin films of conjugated polyrotaxane-poly(ethylene oxide) blends: A scanning force microscopy study - Sardone, L; Williams, C; Anderson, H; Marletta, G; Cacialli, F; Samori, P (2007)
Scanning force microscopy (SFM) is used to study the surface morphology of spin-coated thin films of the ion-transport polymer poly(ethylene oxide) (PEO) blended with either cyclodextrin (CD)-threaded conjugated polyrotaxanes based on poly(4,4′-diphenylene-vinylene) (PDV), β-CD-PDV, or their uninsulated PDV analogues. Both the polyrotaxanes and their blends with PEO are of interest as active materials in light-emitting devices. The SFM analysis of the blended films supported on mica and on indium tin oxide (ITO) reveals in both cases a morphology that reflects the substrate topography on the (sub-)micrometer scale and is characterized by an absence of the surface structure that is usually associated with phase segregation. This observation confirms a good miscibility of the two hydrophilic components, when deposited by using spin-coating, as suggested by the luminescence data on devices and thin films. Clear evidence of phase segregation is instead found when blending PEO with a new organic-soluble conjugated polymer such as a silylated poly(fluorene)-afr-poly(para-phenylene) based polyrotaxane (THS-β-CD-PF- PPP). The results obtained are relevant to the understanding of the factors influencing the interfacial and the intermolecular interactions with a view to optimizing the performance of light-emitting diodes, and light-emitting electrochemical cells based on supramolecularly engineered organic polymers. © 2007 WILEY-VCH Verlag GmbH and Co. KGaA.